2022
DOI: 10.3390/cancers14030507
|View full text |Cite
|
Sign up to set email alerts
|

Preneoplastic Low-Risk Mammary Ductal Lesions (Atypical Ductal Hyperplasia and Ductal Carcinoma In Situ Spectrum): Current Status and Future Directions

Abstract: Intraepithelial mammary ductal neoplasia is a spectrum of disease that varies from atypical ductal hyperplasia (ADH), low-grade (LG), intermediate-grade (IG), to high-grade (HG) ductal carcinoma in situ (DCIS). While ADH has the lowest prognostic significance, HG-DCIS carries the highest risk. Due to widely used screening mammography, the number of intraepithelial mammary ductal neoplastic lesions has increased. The consequence of this practice is the increase in the number of patients who are overdiagnosed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In fact, any B3 lesion with atypia carries a higher risk of missing co-existing malignancy if not excised fully [4, 5]. Thus, such lesions often lead to a recommendation for complete surgical removal [6, 11]. A subset of these tumours can be predicted from mammogram imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, any B3 lesion with atypia carries a higher risk of missing co-existing malignancy if not excised fully [4, 5]. Thus, such lesions often lead to a recommendation for complete surgical removal [6, 11]. A subset of these tumours can be predicted from mammogram imaging.…”
Section: Introductionmentioning
confidence: 99%
“…However, if correctly diagnosed, FEA for example exhibits a very low upgrade rate and lifetime risk of developing IBC [7][8][9]. The similar architectural features of ADH and low grade (LG) DCIS is another diagnostic challenge, and with only the extent of ducts (2 mm size threshold) as a distinguishing feature, ADH bordering on LG DCIS on biopsy confers a high upgrade rate [10,11]. In addition, recent meta analyses showed that ADH alone can be upgraded to IBC after surgical excision from 9 to 28% of the time [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they explained the issues with the design of these studies, particularly with the inherited difficulty in differentiating between ADH and DCIS and between intermediate and high-grade DCIS. A real concern was raised regarding the possibility of leaving significant disease without treatment, such as invasive carcinoma or worse metastatic carcinoma to the axillary lymph node (ALN) [ 1 , 2 ]. Nonetheless, these trials are expected to provide some insight into the natural history of low-risk DCIS.…”
mentioning
confidence: 99%
“…They may also provide some treatment recommendations, particularly for those who may not benefit from an aggressive treatment such as surgical excision with or without RT, and with or without hormonal therapy. It is noted that these trials have experienced difficulty in recruiting patients, as the decision of whether to excise or observe is not simple to make [ 1 ]. Byng et al discussed preferences of treatment strategies among women with low-risk DCIS and oncologists.…”
mentioning
confidence: 99%